2013
DOI: 10.1182/blood-2013-02-482125
|View full text |Cite
|
Sign up to set email alerts
|

Egress of CD19+CD5+ cells into peripheral blood following treatment with the Bruton tyrosine kinase inhibitor ibrutinib in mantle cell lymphoma patients

Abstract: Key Points MCL cells are mobilized into the peripheral blood of patients treated with the BTK inhibitor ibrutinib. Ibrutinib dose-dependently inhibits BCR- and chemokine-mediated adhesion and migration of MCL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
180
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(194 citation statements)
references
References 51 publications
9
180
0
Order By: Relevance
“…[5][6][7][8] In these patients, the BCR signalosome inhibitors ibrutinib and idelalisib induce a rapid decrease in lymphadenopathy, accompanied by transient lymphocytosis. 6,[9][10][11] In CLL and MCL, we have previously demonstrated that ibrutinib and idelalisib target BCR-controlled -and ibrutinib also chemokinecontrolled -integrin-mediated adhesion, resulting in mobilization of the malignant cells from their protective niches in the lymphoid organs into the circulation, followed by lymphoma regression. 5,6,8 Recently, ibrutinib received FDA and EMA approval for the treatment of CLL and MCL, and idelalisib for small lymphocytic lymphoma and follicular lymphoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] In these patients, the BCR signalosome inhibitors ibrutinib and idelalisib induce a rapid decrease in lymphadenopathy, accompanied by transient lymphocytosis. 6,[9][10][11] In CLL and MCL, we have previously demonstrated that ibrutinib and idelalisib target BCR-controlled -and ibrutinib also chemokinecontrolled -integrin-mediated adhesion, resulting in mobilization of the malignant cells from their protective niches in the lymphoid organs into the circulation, followed by lymphoma regression. 5,6,8 Recently, ibrutinib received FDA and EMA approval for the treatment of CLL and MCL, and idelalisib for small lymphocytic lymphoma and follicular lymphoma.…”
mentioning
confidence: 99%
“…6,[9][10][11] In CLL and MCL, we have previously demonstrated that ibrutinib and idelalisib target BCR-controlled -and ibrutinib also chemokinecontrolled -integrin-mediated adhesion, resulting in mobilization of the malignant cells from their protective niches in the lymphoid organs into the circulation, followed by lymphoma regression. 5,6,8 Recently, ibrutinib received FDA and EMA approval for the treatment of CLL and MCL, and idelalisib for small lymphocytic lymphoma and follicular lymphoma. Clinical trials for WM were also very promising, with an overall response rate of 90.5% (n=63) for ibrutinib, 3 and 55-80% (n=9 and n=10) for idelalisib, 1,2 and recently, ibrutinib became the first ever FDA-approved treatment for WM patients.…”
mentioning
confidence: 99%
“…Its expression is tightly regulated during B-cell ontogeny; it is expressed on bone marrow precursors, but not mature B cells. CD38 is expressed on most MCLs (19). In the present study, we show that CD38 is a suitable target for antibody-mediated delivery of therapeutic siRNAs to MCL.…”
mentioning
confidence: 77%
“…This mAb recognizes the surface protein CD38, which is found on immature leukocyte precursors but overexpressed in MCL tumor cells and other B-cell hematological malignancies, such as in chronic lymphocytic leukemia (where it correlates with poor prognosis) and multiple myeloma (27)(28)(29). In MCL, elevated expression of CD38 is correlated with adhesion to stromal cells in lymphoid tissues, a niche considered to be favorable for tumor proliferation (19). MCL tumors resistant to bortezomib, a proteasome inhibitor approved for relapsed MCL, show increased CD38 levels, emphasizing a potential advantage of targeting CD38 (30).…”
Section: Discussionmentioning
confidence: 99%
“…S6). The CXCR4 ligand, CXCL12, induces BTK phosphorylation and downstream MAPK signaling in primary acute myeloid leukemia (AML); the BTK inhibitor drug, Ibrutinib, 39 interrupts the interaction between the tumor cell and the microenvironment that protects leukemic cells, 40 and CXCR4 mutations confer resistance to Ibrutinib. 41 Thus, CXCR4 targeting may regulate TLR4 and BTK pathways both with biological implications in mCRC.…”
Section: Discussionmentioning
confidence: 99%